Diabetes: Chronic Metformin Treatment and Outcome Following Acute Stroke - Akhtar, Naveed; Singh, Rajvir; Kamran, Saadat; Babu, Blessy; Sivasankaran, Shobana; Joseph, Sujatha; Morgan, Deborah; Shuaib, Ashfaq (Frontiers in Neurology, 2022)
Aim: To evaluate if in patients with known diabetes, pre-treatment metformin will lead to less severe stroke, better outcome and lower mortality following acute stroke. Methods: The Qatar stroke database was interrogated for stroke severity and outcome in patients with ischemic stroke. Outcome was compared in non-diabetic patients vs diabetes and in diabetic patients on metformin vs other hypoglycemic agents. NIHSS was used to measure stroke severity and 90-day mRS to determine outcome following acute stroke. Results: 4897 acute stroke patients (none-diabetes: 2740 [56%] and diabetes: 2157 [44%]) were evaluated. There were no significant differences in age, risk factors, stroke severity and type, or thrombolysis between the two groups. At 90-days mRS (shift analysis) showed significantly poor outcome in diabetic patients (p<0.001) but no differences in mortality. In the diabetic group, 1132 patients were on metformin and 1025 on other hypoglycemic agents. mRS shift analysis showed a significantly better outcome in metformin-treated patients (p<0.001) and lower mortality (8.1% vs 4.6% p<0.001). Multivariate negative binomial analyses showed that presence of diabetes negatively affected outcome (90-days mRS) by factor 0.17 (IRR 1.17 [CI 1.08-1.26] p<0.001) when all independent variables were held constant. In diabetic patients, pre-stroke treatment with metformin improved outcome (90-days mRS) by factor 0.14 (IRR 0.86 [CI 0.75-0.97] p=0.006). Conclusion: Similar to previous reports, our study shows that diabetes adversely effects stroke outcome. The use of prior metformin is associated with better outcome in patients with ischemic stroke and results in lower mortality. The positive effects of metformin require further research to better understand its mechanism.